2010
DOI: 10.1523/jneurosci.2527-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Conversion of Odorants in Nasal Mucus Affects Olfactory Glomerular Activation Patterns and Odor Perception

Abstract: Odor information is decoded by a combination of odorant receptors, and thus transformed into discrete spatial patterns of olfactory glomerular activity. It has been found, however, that for some odorants, there are differences between the ligand specificity of an odorant receptor in vitro and its corresponding glomerulus in vivo. These observations led us to hypothesize that there exist prereceptor events that affect the local concentration of a given odorant in the nasal mucus, thus causing the apparent speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
112
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 36 publications
2
112
0
1
Order By: Relevance
“…Because the Baeyer-Villager (B-V) reaction is known to be mediated (62) by oxidative enzymes (e.g., cytochrome P450), which are present in the nasopharyngeal mucus layer (2,32,63,64), and the B-V reaction of deuterated cyclic ketones forming deuterated lactones is known to show an isotope effect (62), such a reaction might affect odor perception of pairs such as 1 and 1-d 28 . Indeed, we have confirmed that 1-d 28 undergoes peracid-mediated B-V oxidation faster than nondeuterated 1, in accord with literature results (62), although a full kinetic analysis in the case of 1/1-d 28 was not possible due to partial overlap of ketone and lactone peaks under GC-MS conditions.…”
Section: Response Of a Human Musk Or To Deuterated And Nondeuteratedmentioning
confidence: 99%
“…Because the Baeyer-Villager (B-V) reaction is known to be mediated (62) by oxidative enzymes (e.g., cytochrome P450), which are present in the nasopharyngeal mucus layer (2,32,63,64), and the B-V reaction of deuterated cyclic ketones forming deuterated lactones is known to show an isotope effect (62), such a reaction might affect odor perception of pairs such as 1 and 1-d 28 . Indeed, we have confirmed that 1-d 28 undergoes peracid-mediated B-V oxidation faster than nondeuterated 1, in accord with literature results (62), although a full kinetic analysis in the case of 1/1-d 28 was not possible due to partial overlap of ketone and lactone peaks under GC-MS conditions.…”
Section: Response Of a Human Musk Or To Deuterated And Nondeuteratedmentioning
confidence: 99%
“…It has been proposed that odorants are degraded and therefore removed by the mucosal enzymes (Thiebaud et al 2013). However, some of the enzymatic reactions in the mucus appear to be fast and to occur before odorants reach the receptor site, resulting in affecting the perception (Nagashima and Touhara 2010). Thus, it remains to be shown (1) how exactly odorants travel from the air space into a receptor-binding site to achieve a concentration high enough to activate the receptor and (2) what is the fate of an odorant after the mission of activating an OR is completed in the mucous layer.…”
Section: Odorant Dynamics and Kineticsmentioning
confidence: 99%
“…Thus, from sequence and functional perspectives, OAT6 belongs to a large family of facilitative solute carriers of the SLC22 family of multispecific organic anion "drug" transporters, the best studied of which are OAT1 and OAT3. Nevertheless, the unique and rather restricted expression pattern of OAT6 in olfactory mucosa raises the interesting possibility of a role for this transporter in delivery of small-molecule xenobiotics across the nasal-epithelial barrier and potential access to the central nervous system (Genter et al, 2009;Nagashima and Touhara, 2010;Thiebaud et al, 2011;Heydel et al, 2013;Nigam et al, 2015). Moreover, in light of common odorant ligands, and because OAT1 is highly expressed in the kidney (whereas OAT6 is highly expressed in olfactory epithelium), it is possible that volatile odorants excreted via OAT1 into the urine interact with olfactory OAT6 in the nasal epithelium (Kaler et al, 2006(Kaler et al, , 2007Wu et al, 2011;Nigam et al, 2015).…”
Section: Introductionmentioning
confidence: 99%